2014
DOI: 10.2106/jbjs.k.00834
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Longer Length of Hospital Stay After Primary Elective Ankle Surgery for End-Stage Ankle Arthritis

Abstract: The patients who are identified with a higher risk of a longer length of stay may warrant better education and more focused perioperative care when designing care pathways and allocating health-care resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…A prospective analysis of patients with end-stage ankle arthritis that underwent elective ankle surgery showed that increased age, female sex, higher American Society of Anesthesiologists grades, multiple medical comorbidities, rheumatoid arthritis, and open surgery were associated with an increased length of stay, but did not specifically evaluate diabetes as a risk factor. 12 Ganesh et al analyzed the impact of diabetes on patient outcomes after ankle fracture using the NIS database and found that diabetes was associated with a significantly increased length of stay (4.7 days vs 3.6 days, P < .001), which is consistent with the results of this study. 8 A prior NIS database analysis of patient outcomes after ankle fracture showed that diabetes was associated with significantly higher hospitalization charges ($12 898 vs $10 794, P < .001).…”
Section: Discussionsupporting
confidence: 88%
“…A prospective analysis of patients with end-stage ankle arthritis that underwent elective ankle surgery showed that increased age, female sex, higher American Society of Anesthesiologists grades, multiple medical comorbidities, rheumatoid arthritis, and open surgery were associated with an increased length of stay, but did not specifically evaluate diabetes as a risk factor. 12 Ganesh et al analyzed the impact of diabetes on patient outcomes after ankle fracture using the NIS database and found that diabetes was associated with a significantly increased length of stay (4.7 days vs 3.6 days, P < .001), which is consistent with the results of this study. 8 A prior NIS database analysis of patient outcomes after ankle fracture showed that diabetes was associated with significantly higher hospitalization charges ($12 898 vs $10 794, P < .001).…”
Section: Discussionsupporting
confidence: 88%
“…For our cohort, LOS was on average 1.0 and 0.5 days higher in readmitted RKA and RHA patients as compared with controls. In the literature focusing on drivers of LOS after primary or revision TJA, greater age, female gender, BMI, days from admission to operation, preoperative and postoperative mobility (including the 36-item Short-Form Health Survey score and need for walking aids), preoperative and postoperative hemoglobin, need for blood transfusion, and ASA class 3/4 [22][23][24]. In an analysis of 23 919 elective noncardiac surgical procedures, Collins et al [25] found nonwhite race, dependent functional status, age N60 years, ASA class 3/4, and severe adverse events (such as need for reoperation) to be drivers of extended LOS (defined similarly as N 75th percentile LOS).…”
Section: Discussionmentioning
confidence: 99%
“…9,22 Previous studies have examined risk factors for increased length of stay related to other orthopedic surgeries; however, to our knowledge, no study has looked at risk factors for increased hospital stay after shoulder arthroplasty. 8,13,34,41 Our analysis of a large nationally representative patient sample allowed us to discern several perioperative factors associated with a prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 99%